Fallow but fertile - Technical Centre for Agricultural and Rural Cooperation (Technical Centre for Agricultural and Rural Cooperation, 1999)
From 13 to 16 April 1999, almost 200 researchers, scientists, decision makers, and development workers from all over Africa and beyond came together in Dakar, Senegal